Conformation and Interactions of Polystyrene and Fullerenes in Dilute to Semidilute Solutions - Dattani,R; Michels,R; Nedoma,AJ; Schweins,R; Westacott,P; Huber,K; Cabral,JT (Macromolecules, 2014)
We report the polymer conformation and fullereneaggregation in a ternary system containing polystyrene, C60, andtoluene measured by small angle neutron, static, and dynamic lightscattering. We investigate polymer concentrations across the diluteand semidilute regime for five polymer molecular weights (Mw =20 kg/mol to 1 Mg/mol), and fullerene concentrations below andabove its miscibility threshold in toluene. We find that the polymerradius of gyration (Rgpoly), hydrodynamic radius (Rh), and themixture correlation length (ξ) remain unchanged upon addition ofC60. The miscibility of C60 in toluene, however, decreases upon addition of polystyrene forming aggregates with a timedependentradius on the order of 100 nm, and this effect is amplified with increasing polymer Mw. Our findings are relevant tothe solution processing of organic photovoltaics, which generally require the effective solubilization of fullerene derivatives andpolymer pairs in this concentration range.